Providing a rest stop during transportation affects the respiratory bacterial microbiota of beef cattle - Uddin, Muhammed Salah; Bumunang, Emmanuel W.; Waldner, Matthew; Schwartzkopf-Genswein, Karen S.; Meléndez, Daniela M.; Niu, Yan D.; Alexander, Trevor W. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundBovine respiratory disease (BRD) is a significant health concern in beef cattle production, leading to substantial economic losses. In North America, beef cattle are frequently transported over long distances for placement into feedlots. The respiratory microbiota of cattle, including pathogens, can change after feedlot entry. However, there is limited information on how bacteria are impacted when cattle are offloaded for a rest stop during transportation.ResultsThis study investigated the effects of a rest stop during transportation on the nasopharyngeal (NP) microbiota of beef cattle. Two separate trials (N = 80 calves per trial) were conducted with treatment groups assigned to rest stop durations of 12 h (Study 1) and 8 h (Study 2), being compared to control animals without a rest stop. In Study 1, cattle were acclimated to a feedlot prior to transportation while in Study 2, cattle were unacclimated. Following transportation and a rest interval, calves were placed into a feedlot and sampled by NP swab periodically for 28 days. Across treatments and time, the most abundant genera included Mycoplasma, Histophilus, Mannheimia, Pasteurella, Moraxella, and Acinetobacter. In both studies, microbial diversity and structure were not affected by providing a rest stop. However, NP swabs from more sampling time points had elevated levels of the BRD-associated genera Mannheimia, Histophilus, and Mycoplasma when the microbiota of calves provided rest were compared to animals given no rest.ConclusionBased solely on the increased abundance of BRD-associated bacteria, providing a rest stop during transportation may be a risk factor for BRD. However, it was not possible to associate rest stop-induced changes in microbiota with disease outcome due to a low incidence of BRD. Further evaluation using large-scale studies will help define the impact of a rest stop during transportation, on BRD pathogens and incidence in feedlots.